Revealing the mechanism of contrasting charge transport properties for phenyl and thienyl substituent organic semiconductors. Issue 8 (12th February 2019) - Zhu, Yanan; Zeng, Xianzhe; Fu, Tianchen; Cao, Yang; Meng, Hong
Abstract : The influence of steric hindrance and HOMO overlap on charge transfer performance for phenyl and thienyl substituent organic semiconductors. Abstract : The aromatic substituents such as phenyl and thienyl have a direct impact on the structure–property relationship of conjugated semiconducting molecules and thus play a significant role in determining the performance of organic thin film transistors (OTFTs). To design a molecule with good charge transport properties, it is essential to understand the charge transfer process. Herein, through the study of two groups of classical OTFT materials with different substituents, we demonstrate the fundamental reasons for the contrasting carrier mobilities between the materials in each group by means of DFT calculations. The results from our theoretical analysis on the two groups of molecules provide very good estimates of their charge transfer properties and the numerical trend from our calculation is consistent with that from the corresponding experimental results. We reveal in detail the impacts of the subtle geometric differences caused by different substituents from two aspects including (i) the significant influence of steric hindrance on reorganization energy and (ii) the overlap of the adjacent molecular orbitals (MOs) on electron coupling. Overall, our systematic investigation into the charge transfer mechanism and geometry effects allows us to employ a reliable theoretical methodology for the prediction of the material performance, which is crucial for the design of high performance OTFT materials.